Peran Ilmu Antropologi bagi Karya Misi Gereja: Sebuah Studi Interdisipliner bagi Penerapan Pelayanan Pastoral dan Kateketik Gereja - Randa, Mayolus D.I. Bhatara; Zandro, Agrindo (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
The missionary work of the Church today often experiences deadlock and even failure due to the work of the wrong mission strategy, not on target, or not following the context of the lives of the faithful. To realize an appropriate and effective mission, the Church needs to conduct an interdisciplinary study between the theology of mission and other sciences, including anthropology. This science can provide accurate and efficient information related to the condition of the people so that the mission of the Church can truly enter the context of the lives of the faithful in a particular area and thus the gospel of truth and joy can be felt by the people. The purpose of this study is to describe the meaning and important role of anthropology, especially applied anthropology for the mission of the Church today, namely in pastoral and catechetical services. The methodology used is a qualitative method by applying a literature study, namely research on books and scientific articles as well as related Church documents. This study found that the science of anthropology is very useful for the mission of the church, especially anthropology has contributed to developing the treasures of Christian theology. The unique contribution of this study is contextual and up-to-date knowledge about mission strategies that can embrace the people of God in all places and times.